O fenômeno urbano como condição para a dinamização socioespacial dos municípios paranaenses da região do Lago de Itaipu - Graff, Vânia Dirley (2013)
This study aims to analyze the urbanization of cities of the region surrounding Itaipu Lake, located in the West of Paraná State, through its socio-spatial dynamics, established from the construction of Itaipu Hydroelectric Power Plant. The survey and interpretation of economic data showed that the cities have different rates of economic development and many of them lack of urban infrastructure. In other words, while some cities have economic sectors highly diversified and representative, others, in contrast, require greater economic dynamism. To come to these results, the methodology used was based on bibliographical/theoretical studies about the concept of region, network, urbanization of society, regional urban planning and urban landscape. Regarding the collection of data about the object of this study, information from IBGE, Ipardes, municipal departments, commercial and industrial associations were used. Aside from that, the interviews consisted of a last, but not least, methodology, performed with some municipal departments linked to Planning, Trade and Industry, to the sector Public Works and Services, the coordinators of Municipal Master Plans, as well as representative of the regional political entity, the Association of Municipalities of West Paraná (Amop). In general, the cities make use of various funding sources of municipal, state and federal areas, but the lack of regional planning and urban infrastructure also appear as obstacles to further development